Keterkaitan Antara Senam Hamil Terhadap Kualitas Tidur Ibu Hamil di TPMB Suriyanti Kota Makassar - Ayu Syah Putri; Umi Kalsum; Tri Rikhaniarti M (LPPM Institut Pendidikan Nusantara Global, 2024)
Pregnancy is a period accompanied by various physiological and psychological changes that can affect the sleep quality of pregnant women. Sleep disorders that occur during pregnancy can impact the health of the mother and fetus. One non-pharmacological effort that can be done to improve sleep quality is pregnancy exercise. Purpose: This study aims to determine the relationship between pregnancy exercise and sleep quality in pregnant women. This study used an analytical design with a cross-sectional approach. The study sample consisted of 35 pregnant women selected using a purposive sampling technique according to the established inclusion criteria. Data were collected using a questionnaire regarding participation in pregnancy exercise and sleep quality of pregnant women, then analyzed using the Mc Nemar test. Results: Before pregnancy exercise, most respondents had poor sleep quality as many as 22 respondents (62.9%). After the intervention, there was an increase in sleep quality to good in 28 respondents (80%), while poor sleep quality decreased to 7 respondents (20%). The results of the Mc Nemar test showed a p-value = 0.000 (p <0.05), which indicates a significant difference between before and after pregnancy exercise, meaning there is a significant relationship between pregnancy exercise and the sleep quality of pregnant women at TPMB Suriyanti Makassar City. In conclusion, there is a significant correlation between prenatal exercise and sleep quality for pregnant women. Pregnant women who regularly participate in prenatal exercise tend to have better sleep quality compared to those who do not. Therefore, prenatal exercise can be recommended as a non-pharmacological intervention to improve sleep quality during pregnancy.